Word and wisdom in the ecclesiology of Louis Bouyer - Yap, J (2003)
The subject of this study is the ecclesiology of Louis Bouyer of the Oratory. The basic claim of the thesis is that his doctrine of the Church is central to his theological project, second only to his preponderant gaze upon the mystery of the Trinity. Bouyer's ecclesiological vision is specifically driven by the twin motifs of 'Word' and 'Wisdom'. The deep dogmatic material that lies at the heart of his doctrine is the Church's dependence on Christ, who is both Word and Wisdom. The Church is creatura verbi divini and equally creatura sapientiae divinae. It is constituted by the divine Word, and destined by the divine Wisdom for glory and union with God. The combination of a salvation-historical and christologically sacramental 'Word-ecclesiology', and a properly trinitarian and eschatologically oriented 'Wisdom-ecclesiology', is what distinguishes Bouyer's doctrine of the Church. Chapter One sets the stage for Bouyer's Word-based ecclesiology through an exposition of his reinforced understanding of the 'Word of God'. Chapter Two traces the Word's crucial development into the Christian 'mystery', and finds that it is none other than Jesus Christ and his saving cross. In turn, the mystery must be embodied in the liturgy, in which it is perpetually proclaimed by and actualized hi the Church. Chapter Three then presents Bouyer's Word-ecclesiology in a twofold articulation: the 'Church of the Word' and the 'Word in the Church'. Chapter Four recognizes a second mode of ecclesiological reflection in Bouyer through his Wisdom-motif which penetrates and complements the dominant logocentric perspective. Chapter Five finally argues that Bouyer's construal of the Church's principal actions (liturgical celebration, evangelical witness, and the total life of prayer and Christian discipleship) is consistent with his christological and trinitarian horizon, and that these ecclesial actions respond most appropriately to the divine initiative manifested in the Word and Wisdom.